PRN OPINION PAPER: Application of precision medicine across pharmacy specialty areas. Issue 3 (24th April 2019) - Caudle, Kelly E.; Gammal, Roseann S.; Karnes, Jason H.; Afanasjeva, Janna; Anderson, Keri C.; Barreto, Erin F.; Beavers, Craig; Bhat, Shubha; Birrer, Kara L.; Chahine, Elias B.; Ensor, Christopher R.; Flowers, Stephanie A.; et al.
Abstract : Clinical pharmacists have been incorporating precision medicine into practice for decades. Drug selection and dosing based on patient‐specific clinical factors such as age, weight, renal function, drug interactions, plasma drug concentrations, and diet are expected as part of routine clinical practice. Newer concepts of precision medicine such as pharmacogenomics have recently been implemented into clinical care, while other concepts such as epigenetics and pharmacomicrobiomics still predominantly exist in the research area but clinical translation is expected in the future. The purpose of this paper is to describe current and emerging aspects of precision medicine as it relates to clinical pharmacy across a variety of specialty areas of practice, with perspectives from the American College of Clinical Pharmacy Practice and Research Network membership.